O exercício do poder disciplinar e as garantias do contraditório e da ampla defesa: a aplicabilidade do artigo 5º, LV, da Constituição Federal de 1988 às relações privadas de emprego - Supioni Junior, Claudimir (2013)
This report publishes research that has adopted as its central object the applicability of the assurances of the contradictory and the legal defense before the disciplinary power of the private employer. The research focused on the study of the effectiveness of the Article 5th, LV, of the Federal Constitution of 1988, its incidence contours, its effects as standard of fundamental rights and the peculiarities of its application in the employment relationship. The research´s central problem was facing by two perspectives: Initially, was studied the applicability of the constitutional provision through the lens of modern constitutional theory, adopting, as the main theoretical, the thesis of constitutional effectiveness of José Afonso da Silva. At second step, without exclusively, was analyzed the problem under the postulates of contemporary constitutionalism and theory of fundamental rights. The research method was the critical revision of the doctrine tangential to the topic, the investigation of primary sources of constitutional legislative process, the jurisprudence, the foreign legislation and the documents published by international organizations. The search result is the postulate that the constitutional guarantees of adversarial and legal defense have immediate irradiation in private relations governed by the Direct Labour ensured by complete eficacial and effectiveness horizontal of the rule inserted in Article 5, LV, of the Federal Constitution 1988, not depending of any legislation or legislative change. To respect the constitutional provision, an employer who intends to sanction or dismiss the worker with a just cause argument must previously assure to him the exercise of the assurances of the contradictory and the legal defense, under penalty of nullity sanction imposed by lack of essential validity. In the case of dismission by just cause, the disrespect to the assurances implies consider the serious lack ineffectual, changing the argument of dismission for unjust type, unless the employee has obtained provisional stability, in which case will be possible think on reinstatement of the worker